Implementasi User Experience Pada E-Commerce Petshop Online - Rian Rasyidhi; Agung Triayudi; Agus Iskandar (JURIKOM (Jurnal Riset Komputer), 2023)
In the current era of globalization, the use of technology is a necessity in every part of today's life. with the development of technology that is used to facilitate life, especially in transaction activities between sellers and buyers Information systems and information technology are also developing in line with the community's need for information technology, one form of information technology in transaction needs is E-Commerce or electronic commerce. Even before the covid 19 outbreak, e-commerce in Indonesia was able to attract many customers. E-commerce is also one of the main reasons why Indonesia has the largest digital economy in Southeast Asia. Therefore, the influence of the user interface and user experience in making websites plays an important role, so that users can feel comfortable and feel every feature used. In this study, researchers applied the Design Thinking approach to create an online pet shop website, and the results of their research used usability testing using the maze website. At the end of the analysis process, the learning outcomes were 88% and the memory results were 96%. overall result score of 92% for overall UI performance and user experience of online pet shop website